Corrosion properties of AlxCoCrFeNiTi0·5 high entropy alloys in 0·5M H2SO4 aqueous solution. (July 2014) - Zhang, J. J.; Yin, X. L.; Dong, Y.; Lu, Y. P.; Jiang, L.; Wang, T. M.; Li, T. J.
Abstract : In previous research, Alx CoCrFeNiTi0·5 high entropy alloys with various amounts of aluminium had shown many excellent mechanical performances, but few attempts were made to characterise the corrosion performance. Therefore, the purpose of this study was to investigate that of the Al x CoCrFeNiTi0·5 ( x = 0, 0·5, 1·0) alloy system in an aqueous solution of 0·5M H2 SO4 at room temperature with the analysis of potentiodynamic polarisation scanning, corrosion surface morphology and electrochemical impedance spectra. It was verified that a high content of Al enhanced the corrosion resistance of the alloys by simultaneously increasing the corrosion potential and decreasing the corrosion current density, also restraining the tendency of pitting corrosion. When x = 0·5 and 1, the alloys had a better corrosion behaviour compared with 304 stainless steel. The equivalent circuits were obtained from the results of EIS tests. They clearly revealed that the existence of a passive film and the difficulty of the resultant diffusion were both important factors to the electrochemical reaction process. This study also demonstrated that constant potential treatment at 0·75 V clearly enhances the corrosion resistance of the alloys.